Pengaruh Persepsi Keadilan terhadapKinerja Distributor PT X dengan Ketergantungan sebagai Variabel Moderating - Hertanto, Icuk; Witoyo, Ade (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: PT. X companies engaged in the national cement productionsector which are the market leaders in Indonesia which control the islandsof Java, Bali, Kalimantan and parts of Eastern Indonesia. The result of thisproduct tends to be a commodity product. So, to maintain market control isto maintain the level of availability of cement products. With suchchallenges, PT. X must maintain good relations with its distribution network.One important factor in maintaining good relations between suppliers andbuyers is the Perception of Organizational Justice that exists in both. Thepurpose of this study was to analyze the effect of perceptions oforganizational justice on the performance of the distributors of PT. X withdependence as moderating variable. This research is a quantitative studywith a total population of all distributors of PT. X. This study concludes thatorganizational justice has a positive effect on distributor performance, andthis influence is not moderated by dependency.Keywords: distributor performance, procedural justice, distributive justice,interactional justice, organizational justice, dependency.